Spectral F-Test power evaluation in the EEG during intermittent photic stimulaton Avaliação do teste-F espectral do EEG durante fotoestimulação intermitente - Antonio Mauricio F. L. Miranda de Sá; Mauricio Cagy; Vladimir V. Lazarev; Antonio Fernando C. Infantosi (Arquivos de Neuro-Psiquiatria)
Intermittent photic stimulation (IPS) is an important functional test, which can induce the photic driving in the electroencephalogram (EEG). It is capable of enhancing latent oscillation’s manifestations not present in the resting EEG. However, for adequate quantitative evaluation of the photic driving, these changes should be assessed on a statistical basis. With this aim, the sampling distribution of spectral F test was investigated. On this basis, confidence limits of the SFT-estimate could be obtained for different practical situations, in which the signal-to-noise ratio and the number of epochs used in the estimation may vary. The technique was applied to the EEG of 10 normal subjects during IPS, and allowed detecting responses not only at the fundamental IPS frequency but also at higher harmonics. It also permitted to assess the strength of the photic driving responses and to compare them in different derivations and in different subjects. A fotoestimulação intermitente (FEI) é um importante teste functional, que pode induzir o fotorecrutamento no eletroencefalograma (EEG), sendo capaz de realçar manifestações latentes de oscilações não observadas no EEG de repouso. Entretanto, para uma análise quantitativa adequada do fotorecrutamento, tais alterações devem ser avaliadas com base estatística. Assim, a distribuição de probabilidade do teste-F espectral (TFE) foi investigada. Neste sentido, limites de confiança para a estimativa do TFE puderam ser obtidos para diferentes situações práticas, nas quais a razão sinal-ruído e o número de épocas usadas na estimação podem variar. A técnica foi aplicada ao EEG de 10 sujeitos normais durante FEI, e permitiu a detecção de respostas não somente na freqüência fundamental da FEI como também em seus harmônicos. Além disso, permitiu avaliar o grau de fotorecrutamento entre derivações distintas e entre diferentes sujeitos.